Medicinal Aroids Conservation: A Case Study Of Floral Garden, School Of Biological Sciences, Universiti Sains Malaysia. - Sulaiman, Baharuddin; Mansor, Mashhor (2002)
The aroids are monocotyledonous herbaceous plants, which are widely found in tropical countries. This Araceae family has played an important role not only in botanical world but also in economical aspects such as by providing medicinal resources. The medicinal properties, which proved to have a curative effect on certain diseases, indicate that these species have a potential value in medicinal industries.